FinTech and the customer experience: How to embrace change in macedonian banking industry? - Snezhana Hristova; Dusica Stevcevska-Srbinoska; Stefan Tanevski; Igor Spasoski (University American College Skopje, 2022)
Over the last decade, modern, disruptive innovation and FinTech services have been developing rapidly and are becoming widely used in the banking industry, thereby transforming financial services for customers with both positive and negative implications. Our paper contributes to identifying the dimensions, the determinants and the outcomes of customer experience in FinTech, while from a banking sector perspective, we demonstrate how banks can better integrate FinTech and customer experience in their business models. In section 1 of the paper, we present a review of FinTech developments in the Macedonian banking industry and we explore how FinTech is reshaping the financial services market. Moreover, we assess if and howMacedonian banks can be better 'digitalized or disrupted' in a Fintech driven future. Some of the key technologies that are elaborated with a focus on banks are: electronic banking and e-trade, digitalization, NFC technology, blockchain technology and many other technologal aspects. In Section 2 we present a review of customer experiences and the ongoing degree of innovative infrastructure and client-based approaches with a focus on clients' outlook of the banking system. The results show that the improved banking infrastructure and new innovative technology-based services are vital for building trustworthy client relationships which are crucial for adaptability and survival in the era of digitalization. The findings also provide more evidence on the current trends, problems and opportunities offered by FinTech to the banking sector and the possible challenges to be faced on its adaptation.
Keywords: O30; G2; 330; Fintech; Technology; Financial services; Customer behavior; Online banking